2016
DOI: 10.1088/0953-8984/28/5/055503
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic spin-splitting in quantum wells with a tilted magnetic field

Abstract: This work aims to investigate the effects of magnetic field strength and direction on the electronic properties and optical response of GaAs/AlGaAs-based heterostructures. An investigation of the excitonic spin-splitting of a disordered multiple quantum well embedded in a wide parabolic quantum well is presented. The results for polarization-resolved photoluminescence show that the magnetic field dependencies of the excitonic spin-splitting and photoluminescence linewidth are crucially sensitive to magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Symbols: perturbation theory from equation (22), solid lines the Bubnov-Galerkin method. 4 We have obtained the same result with the basis { } QW in a tilted magnetic field [13,23]. In figure 3, we plot the conduction band energy levels results as a function of the intensity of the magnetic field considering quantum numbers = = n n 0, 1 z and = = n n 10, 4 z and different angles θ = 0 , 30 , 60 , and 90 .…”
Section: B-g Approachmentioning
confidence: 59%
See 1 more Smart Citation
“…Symbols: perturbation theory from equation (22), solid lines the Bubnov-Galerkin method. 4 We have obtained the same result with the basis { } QW in a tilted magnetic field [13,23]. In figure 3, we plot the conduction band energy levels results as a function of the intensity of the magnetic field considering quantum numbers = = n n 0, 1 z and = = n n 10, 4 z and different angles θ = 0 , 30 , 60 , and 90 .…”
Section: B-g Approachmentioning
confidence: 59%
“…On the other hand, when the magnetic field is applied in an arbitrary direction, the solution is no longer separable by a product of functions of individual variables and closer analytical solutions are no longer available, although some numerical procedures have been used in the past [11][12][13][14][15]. Moreover, a semiclassical approximation has been employed to study the Shubnikov-de Haas and magento-inter-subband oscillations observed in a QW in a tilted magnetic field [16].…”
Section: Introductionmentioning
confidence: 99%